2021
DOI: 10.3389/fsufs.2021.674767
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Persistence of Foodborne Pathogens in Manure-Amended Soils and Prevalence on Fresh Produce in Certified Organic Farms: A Multi-Regional Baseline Analysis

Abstract: Biological soil amendments of animal origin (BSAAOs), including untreated (e.g., raw or aged manure, or incompletely composted manure) and treated animal products (e.g., compost), are used for crop production and as part of soil health management. Application of BSAAO's must be done cautiously, as raw manure commonly contains enteric foodborne pathogens that can potentially contaminate edible produce that may be consumed without cooking. USDA National Organic Program (NOP) certified production systems follow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(70 citation statements)
references
References 69 publications
4
62
4
Order By: Relevance
“…The majority of the Campylobacter isolates (57.3%) from this study possessed multiple drug resistance genes (especially, blaOXA-61 , tetO , and aadE ) based on conventional PCR analysis. Thus, our previous study, as well as studies conducted by other groups, have highlighted the potential public health and food safety risks associated with the use of biological amendments in SSCF ( Ramos et al, 2019 , 2021 ; Black et al, 2021 ; Hailu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 76%
“…The majority of the Campylobacter isolates (57.3%) from this study possessed multiple drug resistance genes (especially, blaOXA-61 , tetO , and aadE ) based on conventional PCR analysis. Thus, our previous study, as well as studies conducted by other groups, have highlighted the potential public health and food safety risks associated with the use of biological amendments in SSCF ( Ramos et al, 2019 , 2021 ; Black et al, 2021 ; Hailu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 76%
“…A 21-month longitudinal, multi-regional field study was conducted on 19 USDA-NOP certified farms located in four USA regions (California, Minnesota, Maine, and Maryland) during two growing seasons (March 2017-December 2018. Details on the recruitment, study design and farm enrollment can be found in a previous publication (Ramos et al, 2021). Briefly, farms were enrolled based on the following criteria: (1) certified USDA-NOP fresh produce farm, (2) use of untreated manure (i.e., raw or untreated manure), (3) grow at least one of the following fresh crops: leafy greens, root vegetables, and/or fruits, (4) willingness to participate and provide biological samples (raw manure, soil, irrigation water, and fresh produce) and information about their farm management practices and location.…”
Section: Study Design and Field Sample Collectionmentioning
confidence: 99%
“…The main reason is the difference between the recommended treatment procedures by the authorities and their practical use. For example, in a recent analysis, Ramos et al (2021) reported that farmers frequently consider the manure aging (storage time needed to reduce the manure pathogenicity) as composting thus introducing live microorganisms existing in the “treated” material into the soil. Moreover, particularly in Spain, illegal or sub-standard landfilling is still widespread practice with all risks of water, air, and soil contamination and potential health problems for animals and humans ( EC Country Report Spain, 2019 ).…”
Section: Risks Of Traditional Microorganism-bearing Fertilizersmentioning
confidence: 99%
“…For these reasons, and particularly in case of factory farming, it is recommended to clean manure, normally by biological or thermal treatment ( Venglovsky et al, 2006 ). In any case, management of manure during storage and further treatment (e.g., by composting) and its proximity to plants from one side, and the always existing possibility of runoff, formation of contaminated dust, and animal movements from the manure storage to crop fields, on the other side, should be an important consideration when analyzing all safety risks on farm sites ( Ramos et al, 2021 ).…”
Section: Risks Of Traditional Microorganism-bearing Fertilizersmentioning
confidence: 99%